Sidewalk theatre presents 'How the vote was won' (1978)
Silhouette of two 'suffragettes' holding flags with the female suffrage campaign colours Poster advertising the Sidewalk Theatre tour of play 'How the vote was won', celebrating 50 years since the female suffrage. Printed by Women in Print PO-1561